General views on treatment technologies for patients with incisional ventral hernia - E. E. Lukoyanychev; S. G. Izmajlov; V. A. Emelyanov; O. S. Kolchina; A. I. Rotkov; M. N. Kiselyov (Исследования и практика в медицине)
Nowadays, the problem of surgical treatment of incisional ventral hernia (IVH) still remains significant. According to the statistical data, the number of patients with postoperative ventral hernias has increased by more than 9 times over the past 25 years. Experts offer many solutions to this problem every year and the surgeon have to find the best method of postoperative rehabilitation in the flow of information. Academic research databases Google Scholar, CyberLeninka and others were used to search for the relevant literature. The following conclusions were drawn from this review. The etiology of IVH is multifactorial. There is no generally accepted evidence-based gradation of risk factors. There is no unified system for selecting the method of hernia repair of the anterior abdominal wall in patients with IVH. The choice of allotransplant material and the method of hernia repair are often individual. The value of the critical level of intraabdominal pressure have not been specified, however, all authors agree that its monitoring should become routine. The sublay technique remains the "gold standard" of plastic surgery by aponeurotic flap, inlay should be used when sublay is impossible to perform. Onlay should be used as a reserve method. In some situations, combinations of techniques are required. More and more laparoscopy is being introduced in the treatment of IVH as an assistance and in therapy. The introduction of new methods of hernia repair based on the uncontrolled separation of the anatomical structures of the abdominal wall imposes special requirements on surgical technology: plastic material, instrumental and technical support, wound closure and pharmacological support, especially in conditions of increased intra-abdominal pressure and tissue tension. We can use medication of pyrimidine’s row (xymedon) for a better implantation of the mesh implant and to increase the resistance of local tissues.